Insights into the Mechanism of Proliferation on the Special Microbes Mediated by Phenolic Acids in the Radix pseudostellariae Rhizosphere under Continuous Monoculture Regimes - Wu, Hongmiao; Xu, Junjian; Wang, Juanying; Qin, Xianjin; Wu, Linkun; Li, Zhicheng; Lin, Sheng; Lin, Weiwei; Zhu, Quan; Khan, Muhammad U.; Lin, Wenxiong (Frontiers in Plant Science, 2017)
As potent allelochemicals, phenolic acids are believed to be associated with replanting disease and cause microflora shift and structural disorder in the rhizosphere soil of continuously monocultured Radix pseudostellariae. The transcriptome sequencing was used to reveal the mechanisms underlying the differential response of pathogenic bacterium Kosakonia sacchari and beneficial bacterium Bacillus pumilus on their interactions with phenolic acids, the main allelochemicals in root exudates of R. pseudostellariae in the monoculture system. The microbes were inoculated in the pots containing soil and the medicinal plant in this study. The results showed that the addition of beneficial B. pumilus to the two-year planted soil significantly decreased the activity of soil urease, catalase, sucrase, and cellulase and increased the activity of chitinase compared with those in the second-year monocropping rhizosphere soil without any treatment. However, opposite results were obtained when K. sacchari was added. Transcriptome analysis showed that vanillin enhanced glycolysis/gluconeogenesis, fatty acid biosynthesis, pentose phosphate, bacterial chemotaxis, flagellar assembly, and phosphotransferase system pathway in K. sacchari. However, protocatechuic acid, a metabolite produced by K. sacchari from vanillin, had negative effects on the citrate cycle and biosynthesis of novobiocin, phenylalanine, tyrosine, and tryptophan in B. pumilus. Concurrently, the protocatechuic acid decreased the biofilm formation of B. pumilus. These results unveiled the mechanisms how phenolic acids differentially mediate the shifts of microbial flora in rhizosphere soil, leading to the proliferation of pathogenic bacteria (i.e., K. sacchari) and the attenuation of beneficial bacteria (i.e., B. pumilus) under the monocropping system of R. pseudostellariae.